THE POTENTIAL OF EXTRACT OF LEAVES AND FLOWERS OF Lantana camara Linn. AS AN ANTIBACTERIAL FOR CATFISH (Clarias gariepinus) INFECTED BY Aeromonas hydrophila - Indriyani Nur; Afiyfah Fitriani; Asnani Asnani (Indonesian Aquaculture Journal, 2009)
Freshwater catfish culture has been hampered by bacterial diseases. One of the agents of the bacterial disease is Motile Aeromonas Septicemia (MAS). The application of synthetic antibiotics has had some disadvantages such as bacterial resistance and undegradable in water. One of the potential antibacterial herbs is Lantana camara. Information of Lantana as an antibacterial on catfish is still limited. Therefore, the experiment of utilization of Lantana as an antibacterial for catfish should be conducted. The experiment was carried out to evaluate the potential of Lantana extract as an antibacterial of A. hydrophila for catfish. The completely randomized design was applied consisting of four treatments using two parts of the plant, leaves and flowers. The treatments were: A = 1,000 ppm of leaves; B = 2,000 ppm of leaves; C = 1,000 ppm of flowers; D = 2,000 ppm of flowers), and control. Lantana extracts were diluted into each culture media which had been infected with A. hydrophila. Several factors were observed in this experiment such as prevalence with of MAS disease, survival rate, percentage of haematocrites and total of leukocytes of fish blood. The results showed that the fish treated with 2,000 ppm of flowers extract had a lower in prevalence of MAS disease and higher in survival rate than those treated with 1,000 ppm; 2,000 ppm of leaves; and 1,000 ppm of flowers, respectively. However, percentage of haematocrytes and total of leucocytes was not influenced by the extracts from different parts of Lantana plant. In conclusion, 2,000 ppm of Lantana flowers extract might be useful as an antibacterial of A. hydrophila for catfish culture.